Addition of biochar to sewage sludge decreases freely dissolved PAHs content and toxicity of sewage sludge-amended soil. (November 2016) - Stefaniuk, Magdalena; Oleszczuk, Patryk
Abstract: Due to an increased content of polycyclic aromatic hydrocarbons (PAHs) frequently found in sewage sludges, it is necessary to find solutions that will reduce the environmental hazard associated with their presence. The aim of this study was to determine changes of total and freely dissolved concentration of PAHs in sewage sludge-biochar-amended soil. Two different sewage sludges and biochars with varying properties were tested. Biochars (BC) were produced from biogas residues at 400 °C or 600 °C and from willow at 600 °C. The freely dissolved PAH concentration was determined by means of passive sampling using polyoxymethylene (POM). Total and freely dissolved PAH concentration was monitored at the beginning of the experiment and after 90 days of aging of the sewage sludge with the biochar and soil. Apart from chemical evaluation, the effect of biochar addition on the toxicity of the tested materials on bacteria - Vibrio fischeri (Microtox ® ), plants - Lepidium sativum (Phytotestkit F, Phytotoxkit F), and Collembola - Folsomia candida (Collembolan test) was evaluated. The addition of biochar to the sewage sludges decreased the content of Cfree PAHs. A reduction from 11 to 43% of sewage sludge toxicity or positive effects on plants expressed by root growth stimulation from 6 to 25% to the control was also found. The range of reduction of Cfree PAHs and toxicity was dependent on the type of biochar. After 90 days of incubation of the biochars with the sewage sludge in the soil, Cfree PAHs and toxicity were found to further decrease compared to the soil with sewage sludge alone. The obtained results show that the addition of biochar to sewage sludges may significantly reduce the risk associated with their environmental use both in terms of PAH content and toxicity of the materials tested. Graphical abstract: Highlights: The effect of biochar addition to sewage sludges and subsequently to the soil was investigated. Bioavailability of polycyclic aromatic hydrocarbon (PAHs) content and toxicity was evaluated. Addition of biochar to sewage sludge decreased bioavailability of PAHs and toxicity. Biochars produced at 600 °C were more effective comparing to produced at 400 °C. Aging of samples increased the PAHs immobilization and toxicity reduction. Abstract : Biochar decreases freely dissolved PAHs in sewage sludge-amended soil.